2021
DOI: 10.3390/antiox10081198
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins and Renal Oxidative Stress

Abstract: Renal failure is a major health problem that is increasing worldwide. To improve clinical outcomes, we need to understand the basic mechanisms of kidney disease. Aging is a risk factor for the development and progression of kidney disease. Cells develop an imbalance of oxidants and antioxidants as they age, resulting in oxidative stress and the development of kidney damage. Calorie restriction (CR) is recognized as a dietary approach that promotes longevity, reduces oxidative stress, and delays the onset of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 243 publications
(300 reference statements)
1
23
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity Sirtuin (SIRT) family members were located in nuclear and mitochondrial organelles, maintaining redox homeostasis via regulating the oxidative stress-associated genes [38]. Previous publications revealed that SIRTs might also serve as upstream molecules to regulate the expression of ROS generation genes including NADPH oxidases (Nox) and ROS elimination genes including Mnsod in cells [38,39]. As mainly distributed in mitochondria, SIRT3 is linked to a variety of oxidative stress-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity Sirtuin (SIRT) family members were located in nuclear and mitochondrial organelles, maintaining redox homeostasis via regulating the oxidative stress-associated genes [38]. Previous publications revealed that SIRTs might also serve as upstream molecules to regulate the expression of ROS generation genes including NADPH oxidases (Nox) and ROS elimination genes including Mnsod in cells [38,39]. As mainly distributed in mitochondria, SIRT3 is linked to a variety of oxidative stress-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, SIRT1, and the NF-κB axis have important roles in renal damage and oxidative stress [ 58 , 59 ], so we orally administered GKA4 to inhibit cisplatin-induced AKI via the AMPK/SIRT1/NF-κB signaling progress. The relative expression of p-AMPK and p-SIRT1 was reduced in the cisplatin-treated damage, but the oral administration of GKA4 reversed these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a key component of several age-related pathologies, including CVDs and acute CKD, and the role of different pro-oxidant molecules, as well as the therapeutic effects of several antioxidants, have been widely studied both in experimental models and in clinical trials [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Cardiovascular Diseases As the Paradigm Of Age-related Chronic Diseases: Cardiorenal Syndromementioning
confidence: 99%